2012
DOI: 10.1152/japplphysiol.00611.2012
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous atrophy occurs within individual lower limb muscles during 60 days of bed rest

Abstract: To better understand disuse muscle atrophy, via magnetic resonance imaging, we sequentially measured muscle cross-sectional area along the entire length of all individual muscles from the hip to ankle in nine male subjects participating in 60-day head-down tilt bed rest (2nd Berlin BedRest Study; BBR2-2). We hypothesized that individual muscles would not atrophy uniformly along their length such that different regions of an individual muscle would atrophy to different extents. This hypothesis was confirmed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 44 publications
5
69
1
Order By: Relevance
“…Also, other groups reported that adaptation of the muscle volume to resistance training and bed rest is spatially localized within this muscle (Matta et al 2014;Miokovic et al 2012). These localized neural and morphological responses can be partly explained by a unique neuroanatomy, i.e., the proximal and other regions are innervated by different motor nerve branches (Sung et al 2003;Yang and Morris 1999).…”
Section: Discussionmentioning
confidence: 94%
“…Also, other groups reported that adaptation of the muscle volume to resistance training and bed rest is spatially localized within this muscle (Matta et al 2014;Miokovic et al 2012). These localized neural and morphological responses can be partly explained by a unique neuroanatomy, i.e., the proximal and other regions are innervated by different motor nerve branches (Sung et al 2003;Yang and Morris 1999).…”
Section: Discussionmentioning
confidence: 94%
“…Prolonged bed-rest is also a model of clinical disuse 8 and can be informative clinically on which musculature is most affected and hence how to target rehabilitation programmes. While a series of works have examined muscle atrophy in the lower limb in disuse, [9][10][11][12][13][14][15][16][17] yet less is known about atrophy of the deep muscles of the hip and the lower leg. A secondary aim of the current study was to examine which muscles of the lower limb atrophy the most.…”
Section: Introductionmentioning
confidence: 99%
“…26 There are a number of factors that may contribute to the lack of difference in whole muscle size observed between controls and swimmers in this study. These include intermittent rather than continuous exposure to deloading; sufficient land-based training (similar 'past BPAQ' scores to control) to negate deloading related changes; or the inability of measures of whole muscle size (volume) to detect segmental changes within the muscle, 27 or other morphological adaptations such as muscle fibre atrophy or changes in tendon and connective tissue stiffness. 28 These results may have implications on the land-based function of swimmers.…”
Section: Discussionmentioning
confidence: 99%